Dynamic Models for Predicting the Moisture - B. Rahardjo (Indonesian Association of Food Technologists, 1998)
The main problem in storage of dry food chips is water absorption. Dried foods tend to absorb moisture from free air. Flexible packaging can reduce the water absorption on foods and as the result it may prolong the shelf lives of the products. However, most flexible package materials are not fully impermeable. The moisture of the products in the package slowly increases until it reaches the moisture equilibrium. Accordingly, the objectives of this study were to develop mathematical models for predicting and to simulate the estimation of the moisture content of food chips during stored on permeable packages. The mathematical models developed were based on water vapor migration trough a permeable film, rate of moisture sorption by foods, equilibrium moisture content and water mass balance. Samples for the experiment were food chips made from gnetum seeds of local production. The gnetum (emping) chips were placed on stainless steel cups. The mouth of the cups were covered using polypropylene plastics as the package models. The cups were stored in glass bottles. The relative humidities of the storage atmosphere in the bottles were adjusted using saturated solution of salts such that the humidity ranges were between 10% to 95%. The changes of moisture content of the fried chips were observed for about twenty five (25) days until they reach their equilibrium moisture contents. The results indicate that the dynamic models can predict the moisture contents of fried chips in package quite well. The estimation of the water vapor migration trough the plastic film seems slower than the observed moisture absorption especially at low moisture contents.